Access to and quality of elective care: a prospective cohort study using hernia surgery as a tracer condition in 83 countries. (Lancet Glob Health, 2024)
BACKGROUND: Timely and safe elective health care facilitates return to normal activities for patients and prevents emergency admissions. Surgery is a cornerstone of elective care and relies on complex pathways. This study aimed to take a whole-system approach to evaluating access to and quality of elective health care globally, using inguinal hernia as a tracer condition. METHODS: This was a prospective, international, cohort study conducted between Jan 30 and May 21, 2023, in which any hospital performing inguinal hernia repairs was eligible to take part. Consecutive patients of any age undergoing primary inguinal hernia repair were included. A measurement set mapped to the attributes of WHO's Health System Building Blocks was defined to evaluate access (emergency surgery rates, bowel resection rates, and waiting times) and quality (mesh use, day-case rates, and postoperative complications). These were compared across World Bank income groups (high-income, upper-middle-income, lower-middle-income, and low-income countries), adjusted for hospital and country. Factors associated with postoperative complications were explored with a three-level multilevel logistic regression model. FINDINGS: 18 058 patients from 640 hospitals in 83 countries were included, of whom 1287 (7·1%) underwent emergency surgery. Emergency surgery rates increased from high-income to low-income countries (6·8%, 9·7%, 11·4%, 14·2%), accompanied by an increase in bowel resection rates (1·2%, 1·4%, 2·3%, 4·2%). Overall waiting times for elective surgery were similar around the world (median 8·0 months from symptoms to surgery), largely because of delays between symptom onset and diagnosis rather than waiting for treatment. In 14 768 elective operations in adults, mesh use decreased from high-income to low-income countries (97·6%, 94·3%, 80·6%, 61·0%). In patients eligible for day-case surgery (n=12 658), day-case rates were low and variable (50·0%, 38·0%, 42·1%, 44·5%). Complications occurred in 2415 (13·4%) of 18 018 patients and were more common after emergency surgery (adjusted odds ratio 2·06, 95% CI 1·72-2·46) and bowel resection (1·85, 1·31-2·63), and less common after day-case surgery (0·39, 0·34-0·44). INTERPRETATION: This study demonstrates that elective health care is essential to preventing over-reliance on emergency systems. We identified actionable targets for system strengthening: clear referral pathways and increasing mesh repair in lower-income settings, and boosting day-case surgery in all income settings. These measures might strengthen non-surgical pathways too, reducing the burden on society and health services. FUNDING: NIHR Global Health Research Unit on Global Surgery and Portuguese Hernia and Abdominal Wall Society (Sociedade Portuguesa de Hernia e Parede Abdominal).
Keywords: Adolescent; Adult; Aged; Child; Elective Surgical Procedures; Female; Global Health; Health Services Accessibility; Hernia, Inguinal; Herniorrhaphy; Humans; Male; Middle Aged; Postoperative Complications; Prospective Studies; Quality of Health Care; Young Adult